Process of Adoption and Rejection of the Japanese Model by China from the End of the 19th Century till 1937 (Economic and Political Thought, 2014)
The article is devoted to the process of adoption of a Japanese model byChina at the turn of the 19th and the 20th century and its rejection in the years1915–1937. The article presents the influence exerted on the “Middle State”by Japan in that period and its consequences, including the development ofthe communist movement in China.